Retrograde jejunogastric intussusception: A case report and review of the literature - Chao-Man Loi; Shu-Yi Huang; Ying-Da Chen; Shian-Dian Chen; Jiann-Ming Wu; Kuo-Hsin Chen (Asian Journal of Surgery, 2017)
Retrograde jejunogastric intussusception (JGI) is a rare but potentially fatal complication after previous gastrectomy or gastric bypass surgery. Because of the prevalence of bariatric surgery, the number of cases of postoperative intussusception has increased markedly. Here, we present the case of a patient with retrograde jejunogastric intussusception, having a previous history of subtotal gastrectomy and gastrojejunostomy for peptic ulcer disease. Correct preoperative diagnosis was made by plain abdominal film, upper gastrointestinal series, computed tomographic scan, and esophagogastroduodenoscopy. The diagnosis was confirmed by laparoscopic examination.